2016
DOI: 10.1080/10457097.2016.1229563
|View full text |Cite
|
Sign up to set email alerts
|

Statesmanship Beyond the Modern State

Abstract: The concept and ideal of statesmanship have been handed down to us from ancient to modern times, but it has a paradoxical relationship with the modern state. While terminology suggests that statesmanship presupposes the state, in fact it appears rather incongruent with modern (i.e., constitutional, democratic, and bureaucratic) statehood. Nonetheless, statesmanship continues to be promoted and new understandings, such as judicial and administrative statesmanship, have been proposed. Some hope, moreover, that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Democracy, both in its limited meaning of rule by the lower-class many and in its extensive social meaning elaborated by Tocqueville, 29 is not conducive for the emergence and appreciation of statesmanship. 30 Democracy's egalitarian and partisan character, in particular, pose obstacles to these -unless we see, afterwards, that it was really necessary for magnanimous men to intervene and that it turned out to be for the best. 'Democratic statesmanship', though sometimes hailed as an important ideal, 31 seems to remain an oxymoron.…”
Section: Aristotelian Statesmanship and Modern Democracymentioning
confidence: 97%
“…Democracy, both in its limited meaning of rule by the lower-class many and in its extensive social meaning elaborated by Tocqueville, 29 is not conducive for the emergence and appreciation of statesmanship. 30 Democracy's egalitarian and partisan character, in particular, pose obstacles to these -unless we see, afterwards, that it was really necessary for magnanimous men to intervene and that it turned out to be for the best. 'Democratic statesmanship', though sometimes hailed as an important ideal, 31 seems to remain an oxymoron.…”
Section: Aristotelian Statesmanship and Modern Democracymentioning
confidence: 97%
“…Statesmanship can roughly be defined as morally excellent leadership at the polity level. 13 From a philosophical point of view, the character of the statesman, as stated by Edmund Burke 14 , a British political thinker of the 18th century who concluded that the significant difference between a true statesman and a swindler is that the statesman sees the future and acts on established principles and for eternity. In contrast, the swindler only sees the present and acts based on injustice and immorality.…”
Section: The Concept and Nature Of Statesman As Requirements For Cons...mentioning
confidence: 99%
“…Statesmanship is extraordinary by definition and does not fit naturally with everyday politics in a relatively stable and functioning regime. "Stateness" is at odds with statesmanship (Overeem and Bakker 2019).…”
Section: Statesmanship Classical and Modernmentioning
confidence: 99%